HUMAN RIGHTS AND AMERICAN FOREIGN POLICY (The Pretoria Student Law Review, 2021)
American involvement in the international arena vacillates and shifts at a fast pace. Since the terrorist attacks on US soil in 2001, the Bush administration has aggressively returned the US to internationalism. The American interaction on the international stage has always been unique. Currently, as the only true superpower in the international system, the effect of US foreign policy on the global human rights regime is likely to be greater than at any other time in their history. The significant question, then, is to the position, if at all, of human rights concerns within US foreign policy. Ruggie states that international regimes which are closer to a superpower's core security interests will necessarily be stronger than those further away. One may then suppose that regimes which are dominant in the foreign policy of a superpower will be stronger than those less dominant. This article analyses the position of human rights within the current administration in the US in order to determine if US foreign policy concerns itself at all with these issues when making policy decisions.
Keywords: American involvement; international arena; terrorist attacks on US; 2001; US foreign policy; Bush administration; human rights; policy decisions